Bench-To-Bedside and Bedside Back to the Bench; Coordinating Clinical and Experimental Traumatic Brain Injury Studies - Agoston, Denes V.; Bellander, Bo-Michael; Risling, Mårten (Frontiers in Neurology, 2012)
Traumatic brain injury is one of the leading cause of death and long term disability in virtually every country. Advances in neurointensive care have resulted in steadily decreasing morbidity, but the number of individuals with severe long term disability have not changed significantly and the number of moderate disability has shown steady increase over the last 3 decades. Despite years of intensive preclinical research - and millions spent - there are virtually no drugs specifically developed to mitigate the consequences of TBI. Here we discuss some of the existing gaps between clinical and experimental TBI studies that may have contributed to the current status. We do this hoping that clinical, basic, and translational scientists will design and coordinate studies in order to achieve maximum benefits for TBI patients. In conclusion, we suggest to: 1) Develop consensus based guidelines for experimental TBI research, similar to “best practices” in the clinic; 2) Generate a consensus-based template for clinical data collection and deposition as well as for experimental TBI data collection and deposition; 3) Use a systems biology approach and create a database for integrating existing data from basic and clinical research.